Large-Area Photoreceptor Degeneration Model in Rabbits by Photocoagulation and Oxidative Stress in the Retina - Wang, Zhexuan; Feng, Chenli; Yang, Ruyi; Liu, Tingting; Chen, Yin; Chen, Aihua; Yan, Biao; Yuan, Yuanzhi; Zhang, Jiayi (Frontiers in Neuroscience, 2021)
Photocoagulation is used for the treatment of retinal ischemic disease. However, due to the invasive nature of photocoagulation and variety of melanin concentrations between individuals, it is challenging to avoid damaging the adjacent photoreceptors and inducing several side effects. Previous studies indicate the role of laser power, duration, and spot size on retinal lesions, but the effect of interspot distance of the laser pulses needs to be considered in panretinal photocoagulation. In this study, we examine different parameters of photocoagulation on lesions of the retina in rabbit, finding that the lesion level of the outer nuclear layer of the retina depended on the pulse duration and laser spot size, and decreasing interspot distance could completely abolish the photoreceptor layer. The degeneration of the photoreceptor by photocoagulation occurred in 24 h and was not restored afterward. We then conducted panretinal photocoagulation in rabbit and found that oxidative stress was decreased in the inner nuclear layer of the retina, and pupillary light reflex and ERG signals were impaired. Our study could provide a rabbit model to explore the mechanism of photoreceptor degeneration and therapies for the side effects after photocoagulation.